OPTIMIZING THE WAQF MANAGEMENT IN ISLAMIC BOARDING SCHOOLS: A STUDY OF THE BASMALAH FRANCHISE IN INDONESIA - Moch. Iqbal Afandy; Durrotun Nafisah (Al'Adalah, 2022)
Waqf is an alternative for Muslims to donate their endowment for a charitable purpose. This endowment is also usually purposed to build or develop mosques, madrasas, Islamic boarding schools (pesantren), and other Islamic institutions. From the business perspective of Islamic boarding schools, it can mean a capital asset or something that can be used for productive or valuable purposes. The research examines the concept of optimizing waqf in pesantren and analyzes the implementation of management waqf on the Basmalah franchises (Kopontren Basmalah Sidogiri). This article is based on a field study that used a descriptive-analytical approach. The paper concludes that the optimization of waqf on the Basmalah franchise uses the concept of productive waqf. Kopontren Basmalah, based on an Islamic sharia cooperative, accommodates members and investors collectively to develop waqf assets. The management of the Kopontren Sidogiri also facilitates the new branch of the Basmalah store by accommodating various aqad in a profit-sharing system.